The Urgency of Indonesia Social Media Regulation in the Vortex of Terrorism - FX Andy Sutrisno (Pusbindiklatren Bappenas, 2020)
Social media becomes a very important and strategic tool for terrorists to do propaganda, recruitment, funding, and facilitation of other terrorist activities. Both international level and national level, no regulation explicitly regulates the use of social media for terrorism. Since many incidents of terrorism using social media in Indonesia, the more vigorous terrorists’ propaganda and recruitment through social media, and considering opened terrorist access to pursue their targets, especially the youth generation, it is vital to specifically regulate social media and terrorism. Although social media and terrorism issues need to be addressed by the increasing of local government’s role in combating terrorism and the strengthening parental supervision in the use of social media by children, the need for social media and terrorism regulation is an urgent matter to do first, as a guide to tackling the social media use in the vortex of terrorism.